2D structured mesh for simulations of unsteady cavitation around a plane convex hydrofoil. Issue 1 (1st April 2022) - Puga, D; Hidalgo, V; Luo, X
Abstract: The present paper focuses on the influence of the mesh for simulations of unsteady cavitation around a plane convex hydrofoil. A two dimensional structured mesh was generated using free software Gmsh. The span wise size of the hydrofoil was 0.02 of the chord length in the computational domain. The numerical simulation was conducted by using the software OpenFOAM with the k-ω SST SAS turbulence model and the Zwart-Gerber-Belamri cavitation model. The results show that the present numerical method including two dimensional mesh strategy and the SAS turbulence model efficiently represents the unsteady cavitation behaviour around the plane convex hydrofoil, and reproduces the maximum cavity length and the cavitation oscillation compared with the experimental data and the numerical results simulated by implicit LES in a characteristic cycle.